2020
DOI: 10.15421/2020_40
|View full text |Cite
|
Sign up to set email alerts
|

Reducing danger of heavy metals accumulation in winter wheat grain which is grown after leguminous perennial precursor

Abstract: Goal. Assessment of the influence of growing leguminous perennial herbs on the intensity of heavy metals accumulation in winter wheat as in a subsequent crop rotation. Methods. Field, laboratory atomic absorption method, mathematical and statistical processing. Results. cultivation of winter wheat after precursors of Medicago sativa I., Trifolium pratense L., Onobrychis arenaria Kit., Melilotus albus L., Lotus corniculatus L. or Galéga orientalis Lam. leads to a decrease in the content of lead by 1.8-2.5 times… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 26 publications
0
14
0
2
Order By: Relevance
“…Zhou [60] noted the stimulating effect of nitrogen fertilisation (in the form of NH 4 NO 3 ) on the cadmium and lead contents in radishes, carrots, and potatoes. Razanov et al [61] also demonstrated that the use of mineral fertilisation, particularly ammonium nitrate (60 kg ha −1 ), promoted the accumulation of lead, cadmium, and zinc in the leaves and seeds of Silybum marianum L. These authors also noted high rates of accumulation of the analysed elements, which was indicative of their intensive uptake by plants at concentrations much higher than the contents of their mobile forms in the soil. The effect of nitrogen fertilisation on the trace element contents in plants results mainly from the yield-forming action of nitrogen, its effect on the biological value of the yield, and the change in soil pH in the root zone of plants [62].…”
Section: Discussionmentioning
confidence: 93%
“…Zhou [60] noted the stimulating effect of nitrogen fertilisation (in the form of NH 4 NO 3 ) on the cadmium and lead contents in radishes, carrots, and potatoes. Razanov et al [61] also demonstrated that the use of mineral fertilisation, particularly ammonium nitrate (60 kg ha −1 ), promoted the accumulation of lead, cadmium, and zinc in the leaves and seeds of Silybum marianum L. These authors also noted high rates of accumulation of the analysed elements, which was indicative of their intensive uptake by plants at concentrations much higher than the contents of their mobile forms in the soil. The effect of nitrogen fertilisation on the trace element contents in plants results mainly from the yield-forming action of nitrogen, its effect on the biological value of the yield, and the change in soil pH in the root zone of plants [62].…”
Section: Discussionmentioning
confidence: 93%
“…Contaminants, heavy metals in particular, pose a great threat due to their ability to migrate to plants and accumulate in large concentrations. As is known, phytoindicator plants can accumulate in their vegetative mass hundredsand even thousands-fold more toxicants than their concentrations in the soil, depending on their botanical origin (Razanov et al, 2018(Razanov et al, , 2020. Technogenic impact of military action drastically intensifies accumulation of heavy metals in vegetation (Pereira et al, 2022;Razanov et al, 2023).…”
Section: Introductionmentioning
confidence: 99%
“…In recent decades the current environmental crisis has drawn prompt attention to biocentric approaches, in which the ecological imperative is not the subordination of nature to human interests, but coordination, a harmonious combination of human activity and the laws of nature. Such development of relations is preceded by a model that would solve conceptual problems due to forecasts, directing further actions towards the dynamic equilibrium of processes in ecosystems and optimisation of the life state of biodiversity (Razanov et al, 2020). The management of the plant vitality within certain ecosystems, for which methods and concepts based on a complex of structural and functional features of adaptation changes, as adaptive mechanisms to environmental conditions, do not lose their relevance (Kordium et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…The stability of the genotype is calculated by the difference between the maximum and minimum yield and, the lower it is, the higher the stability (stress resistance). An intensive variety is considered to be one that, under optimal growing conditions, each year prevails in seed productivity of all those researched; plastic (capable of variability) is a variety that provides the highest average productivity under different conditions in years of conducting the experiments; a stable variety is the one that has the smallest difference between the maximum and minimum yields, an adaptive variety forms a consistently high, relative to other varieties, seed productivity with genetically determined quality in a wide range of changing weather and anthropogenic conditions (Razanov et al, 2018). Adaptability corresponds to the content of the parameters of ecological plasticity.…”
Section: Introductionmentioning
confidence: 99%